Strengthening the performance of limestone-calcined clay cement (LC3) using nano silica. (18th July 2022) - Lin, Run-Sheng; Oh, Seokhoon; Du, Wei; Wang, Xiao-Yong
Graphical abstract: Highlights: Nano silica can improve the early strength and carbonation resistance of limestone-calcined clay-cement (LC 3 ) mixtures. Nano silica helps to accelerate the hydration rate of LC 3 mixtures. Nano silica improved the electrical resistivity of the LC 3 mixture in the early and late stages. The mechanism of action of nano silica on LC 3 mixtures is highlighted. Abstract: Limestone-calcined clay cement (LC 3 ) is a promising cementitious material for the future; however, it poses the problem of low strength in the early stage, which has not yet been solved. This research proposed to increase the performance of LC 3 through nano silica, especially its early strength and carbonation resistance. The effects of adding 1% and 2% nano silica on the compressive strength, hydration reaction, microstructure, electrical resistivity, and carbonation resistance of LC 3 mixtures were investigated. The experimental results indicated the following: (1) nano silica can significantly improve the compressive strength of LC 3 mixtures, especially the 1-day compressive strength; (2) the results of isothermal calorimetry and thermogravimetric analysis showed that nano silica can significantly accelerate the reaction rate of LC 3 mixtures; (3) with the addition of nano silica, the resistivity and ultrasonic pulse velocity of the LC 3 mixtures increased significantly, and the carbonation resistance was improved, indicating that nano silica can refine its microscopic pore structure and enhance its durability. In general, the addition of nano silica provides the feasibility to overcome the weaknesses of LC 3 concrete (such as low early age strength and low carbonation resistance), enhance the long-term performance, and extend the service life.